Study of radiation protection vestments for maintenance of mobile nuclear power plants - P. A. P. Celestino; G. M. A. A. Sordi (Brazilian Journal of Radiation Sciences, 2023)
Most radiation exposure to personnel comes from inspection, maintenance, and repair within the reactor compartment. The objective of this paper was to discover the garment that, at the same time, presents the best result for the attenuation of ionizing radiation, as well as good ergonomics for the maintenance professional of mobile nuclear plants. For this, market research was carried out and, as a result, nine Radiation Protection Vestments (VPRs) were found, from five different manufacturers and from three countries, the United States, Japan and China; and which are feasible to be acquired. To choose the VPR, the optimization techniques of CIPR 55 were used: Multi-Attribute Utility Analysis and Multi-Criteria Outranking Analysis. Based on the information provided by the manufacturers, five attributes were chosen for comparison: protection cost, percentage of ionizing radiation attenuation, weight, discomfort, and surface decontamination of the vestment. To verify the robustness of the analytical solution, the values of the scaling constants were re-calculated, where it was observed that the analytical solution found is strongly influenced when the protection cost is changed, as it is the highest cost VPR among all those surveyed. The VPR chosen by both optimization techniques was the STEMRAD 360, which has the highest attenuation of ionizing radiation, as well as being the VPR with greater emphasis on ergonomics.